Cadherin-catenin complexes during zebrafish oogenesis: heterotypic junctions between oocytes and follicle cells1 - Cerdà, Joan; Reidenbach, Sonja; Franke, Werner (Biology of reproduction, 1999)
During vertebrate oogenesis, the germ cells and associated somatic cells remain connected by a variety of adhering junctional complexes. However, the molecular composition of these cellular structures is largely unknown. To identify the proteins forming the heterotypic adherens junctions between oocytes and follicle cells in the zebrafish (Danio rerio), the cDNAs encoding αE-catenin and plakoglobin were isolated. Using these cDNAs, in combination with the previously isolated β-catenin cDNA, and antibodies specific for α- and β-catenin, plakoglobin, and N- and E-cadherin, we found differences in catenin and plakoglobin gene expression during oogenesis. The immunolocalization of these plaque proteins, as well as of cadherins, in the ovarian follicle indicated an enrichment of α- and β-catenin and of E-cadherin-like protein(s) in the oocyte cortex, notably at sites of oocyte-follicle cell contacts, suggesting the presence of hitherto unknown heterotypic adherens junctions between these cells. By contrast, plakoglobin and N-cadherin localization was restricted to cell-cell contacts in the follicle cell layer. During oocyte maturation, mRNAs for αE- and β-catenin and plakoglobin accumulated, and all three plaque-forming proteins were stored in unfertilized eggs, either in complexed forms with cadherins or as free cytoplasmic pools. These findings suggest possible roles of these junctional proteins during early embryogenesis.
Gesehen am 11.02.2021